Report on Electoral Law and Electoral Administration in Europe. Synthesis Study on Recurrent Challenges and Problematic Issues. Taken note by the Council of Democratic Elections at its 69th online meeting (7 October 2020) and the Venice Commission at its 124th online Plenary Session (8-9 October 2020) - Krennerich, Michael (2020)
<br